Pertanggungjawaban Debitor Terhadap Kreditor Konkuren Setelah Homologasi Perjanjian Perdamaian Penundaan Kewajiban Pembayaran Utang (PKPU) - Dian Pribadi Sihotang (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
A peace agreement that has been homologated is binding on all creditors who agree to the peace plan in accordance with Article 286 of Law Number 37 of 2004. The debtor is obliged to prove that the peace agreement has been fulfilled by the creditors as per the peace agreement that has been agreed. This research is aimed at analyzing legal certainty regarding the rights of concurrent creditors after homologation has been carried out, the debtor's responsibility if the debtor does not fulfill his promise according to the peace agreement that has been homologated and analyzing the application of the law by the panel of judges in Decision Number 11/Pdt.Sus-PKPU /2017/PN Niaga Medan regarding the responsibility of debtors to concurrent creditors in the implementation of the homologated PKPU peace agreement. This research is normative legal research that is qualitative in nature. Data comes from primary, secondary and tertiary legal materials collected using library research and document study techniques. Primary data as supporting data for normative analysis was collected using the interview method with judges and curators who were determined purposively. Data analysis was carried out using the qualitative normative data analysis method.Based on the research results, it is concluded that legal certainty regarding the rights of concurrent creditors occurs after the homologation of peace agreements which are binding and obtain permanent legal force. If the debtor is negligent and the settlement is canceled, the debtor will lose independence or the debtor will no longer have any interest in controlling or managing his assets. In this regard, the application of the law by the panel of judges in the homologation Decision Number 11/Pdt.Sus-PKPU/2017/PN Niaga Medan was correct with the consideration that the debtor was declared negligent in fulfilling his obligations and canceled the decision to ratify the peace by declaring the debtor to be in bankruptcy with all legal consequences